Caracterização da transição de regimes de escoamento na camada limite noturna sobre diferentes superfícies - Sousa, Édria Valdenice Santos de (2022)
In the present study, the proposal of Acevedo et al. (2021) was applied to a dataset of 63 sites of the AmeriFlux network, installed in regions with 6 different surface classifications. From the application of the methodology, which considers the relationship between local average wind speed and radiation balance, the results show that this behavior occurs over different surfaces. The presence of a linear relationship, between the mean horizontal wind speed (V) and the radiation balance (Rn) was presented in most of the sites, even though, this linear dependence was not observed in approximately 30% of the sites analyzed. The analyses showed that, on average, sites with surfaces characterized as forest and mangrove have the highest coupling strengh (CS), respectively. And when sites are grouped by the same surface classification, and when sites are in the same region, the CS is the same due to the soil thermal properties being the same or similar. Once the soil thermal properties and the topography of the sites are known, it may be possible to determine a universal relationship for the CS, and this relationship can be used by numerical weather and climate prediction models to determine the regime transition of the CLE. Although the present work brings important contributions to the understanding of the dynamics between Vr and Rn, some aspects still need to be understood. In the next steps of this study, it is intended to use the surface use information used by the WRF model, for the calculation of the CS, in the studied dataset. In addition, search for other data sets, which have the full surface description, to determine if it is possible to define an equation for V × Rn, having as angular constant the surface coupling forcing.